PELATIHAN KETERAMPILAN BAHASA INGGRIS BAGI TENAGA PENDIDIK - Tazkiyatunnafs Elhawwa (LPPM IAI Hasanuddin Pare-Kediri, 2026)
English is the basis for the development of learning that must be improved. For participants, English Language Training is one of the efforts that can be made to improve English proficiency which is useful for supporting the ability to communicate both orally and in writing. This training was carried out for 40 hours (20 days x 2 hours) through several methods such as lectures, discussions, demonstrations/demonstrations, hands-on practice, and working on questions. The results of this community service activity received a positive response from the agency, especially because this program was in accordance with their needs. This could be seen from the motivation of the trainees to take part in the training process quite enthusiastically, indicating a desire to improve their ability to master English and understand the importance of English. Keywords: language skills; English training; basic skills.